Strategic Dynamics of Mergers and Acquisitions in the Tourism and Hotel Industry: Insights, Challenges, and Opportunities - Prevolšek, Denis (Turizam, 2025)
Mergers and acquisitions (M&A) serve as strategic mechanisms for growth, resource optimization, and competitive positioning, particularly within the dynamic and diverse tourism industry, including the hotel sector. This case study synthesizes insights from five research papers to analyze critical factors influencing M&A in subsectors such as hotels, travel agencies, and cruise companies. Using a meta-analytical methodology, the study explores themes including determinants of success, the impact of institutional environments, strategic decision-making, and temporal perspectives on performance outcomes. Findings highlight the pivotal role of payment methods (cash versus stock), with cash payments generally preferred in stable environments for reducing uncertainty and enhancing trust. Institutional and regulatory factors significantly influence payment strategies and post-merger success. Resource criticality drives strategic decisions, such as vertical integration in the hotel and cruise sectors, while partnerships mitigate risks in high-stakes scenarios. Although M&A activities often result in short-term financial volatility, effective post-merger integration and resource optimization, exemplified by methodologies like Data Envelopment Analysis (DEA), lead to long-term efficiencies and profitability. Practical recommendations for managers include aligning payment methods with institutional contexts, prioritizing detailed integration plans, leveraging alliances to mitigate risks, and tailoring strategies to the unique needs of specific subsectors such as hotels. Academically, the study contributes to the understanding of M&A by synthesizing diverse methodologies and addressing underexplored areas, such as the dynamics of hotel-sector efficiencies. While recognizing limitations, including reliance on secondary data and a narrow scope, this research offers actionable insights and paves the way for further exploration of evolving trends in M&A strategies across the tourism industry.
Keywords: Mergers and acquisitions (M&A); Tourism industry; Payment methods; Institutional environments; Strategic decision-making; Resource optimization; Post-merger integration